A new record of Chaerephone johorensis at Mount Jerai, Kedah, Malaysia - Isham, Azhar; Siti Hajar, Muhammad Daud; Jayaraj Vijaya, Kumaran (Malayan Nature JournaI, 2013)
Chaerephonjohorensis, a wrinkled lipped bat ofthe family molossidae was recorded in mount Jerai, Kedah. this new record for Kedah was caught at hutan Lipur air terjun Batu hampar. this species was previously recorded in Krau wildlife reserve, taman negara, Johor (type locality) and a single locality in sumatra. this new record extends the current distribution of this species right up to northwest of Peninsular malaysia. Other notable discovery includes 25 species of small mammals.